2012
DOI: 10.7314/apjcp.2012.13.1.371
|View full text |Cite
|
Sign up to set email alerts
|

5'-CpG Island Promoter Hypermethylation of the CAV-1 Gene in Breast Cancer Patients of Kashmir

Abstract: Background: Caveolin-1 (CAV-1), encoding the structural component of cellular caveolae, is a suggested tumor suppressor gene involved in cell signalling. Aberrant promoter methylation of CAV-1 is associated with inactivation of expression. We previously observed CAV-1 mutations in breast cancers and therefore devised this study to examine the hypermethylation status of the promoter region of CAV-1 with reference to breast cancer progression and development. Methods: Hypermethylation status of CAV-1 was analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…In human breast cancer cells, 5′ promoter of cav-1 is methylated as opposed to normal human mammary epithelial cells (41, 45). In studies on clinical samples from breast tumors, hypermethylation of Cav1 promoter was accompanied by the downregulation of cav-1 expression in comparison to the adjacent unaffected breast tissue (42, 46). Gem has been shown to function as DNA methyltransferase inhibitor reactivating epigenetically silenced genes (47).…”
Section: Discussionmentioning
confidence: 99%
“…In human breast cancer cells, 5′ promoter of cav-1 is methylated as opposed to normal human mammary epithelial cells (41, 45). In studies on clinical samples from breast tumors, hypermethylation of Cav1 promoter was accompanied by the downregulation of cav-1 expression in comparison to the adjacent unaffected breast tissue (42, 46). Gem has been shown to function as DNA methyltransferase inhibitor reactivating epigenetically silenced genes (47).…”
Section: Discussionmentioning
confidence: 99%
“…Cav-1 is a suggested tumor suppressor gene involved in cell signalling (Syeed et al, 2012). Roles of Cav-1 protein in carcinoma development are compartmentdependent and tumor dependent (Williams and Lisanti, 2005;Sotgia et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These animals are resistant to diet-induced obesity, present associated white adipose tissue atrophy and exhibit reduced fat pads, hypertriglyceridemia, hyperinsulinemia and insulin resistance [15]. Previous studies have reported that, in some tumors, Cav-1 expression is regulated by the methylation of its promoter [16][17].…”
Section: Introductionmentioning
confidence: 99%